Combine Target Extraction and Enhancement Methods to Fuse Infrared and LLL Images - Yong Chen; Xiong Jie; Huan-lin Liu; Qiang Fan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
For getting the useful object information from infrared image and mining more detail of low light level (LLL) image, we propose a new fusion method based on segmentation and enhancement methods in the paper. First, using 2D maximum entropy method to segment the original infrared image for extracting infrared target, enhancing original LLL image by Zadeh transform for mining more detail information, on the basis of the segmented map to fuse the enhanced LLL image and original infrared image. Then, original infrared image, the enhanced LLL image and the first fused image are used to realize fusion in non-subsampled contourlet transform (NSCT) domain, we get the second fused image. By contrast of experiments, the fused image of the second fused method’s visual effect is better than other methods’ from the literature. Finally, Objective evaluation is used to evaluate the fused images’ quality, its results also show that the proposed method can pop target information, improve fused image’s resolution and contrast.